Peta Ide sebagai Strategi Menulis Deskriptif Teks pada Siswa Pontren Al-Falah - Magvirah El Walidayni Kau; Irmawaty Umar; Nurlaila Husain; Indri Wirahmi Bay; Sri Widyarti Ali; Helena Badu; Fahria Malabar (Universitas Negeri Gorontalo, 2022)
AbstractWriting is a simple and enjoyable activity. Students can be helped with various strategies to express their ideas, thoughts, and feelings in writing. This service is provided to assist Madrasah Aliyah Al-Falah students in writing descriptive texts using mind mapping strategy. The students liked the strategy because it motivated them to write descriptive texts in a fun way. Mind mapping is still the recommended strategy for writing descriptive texts because it can create a pleasant classroom environment, encourage students to be more creative in expressing their ideas, and improve writing results.Keywords: descriptive text, mind mapping